2011
DOI: 10.1016/j.juro.2010.09.098
|View full text |Cite
|
Sign up to set email alerts
|

Size Does Matter: Donor Renal Volume Predicts Recipient Function Following Live Donor Renal Transplantation

Abstract: Larger kidney volumes calculated using 3-dimensional computerized tomography with volume calculating software are correlated with lower recipient nadir and 1-year serum creatinine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…Larger kidney volumes are correlated with improved kidney function at 1 year (45). Renal length and volumes also correlate with recipient renal function up to 36 months after transplantation.…”
Section: Computed Tomographymentioning
confidence: 84%
See 1 more Smart Citation
“…Larger kidney volumes are correlated with improved kidney function at 1 year (45). Renal length and volumes also correlate with recipient renal function up to 36 months after transplantation.…”
Section: Computed Tomographymentioning
confidence: 84%
“…Renal length and volumes also correlate with recipient renal function up to 36 months after transplantation. A low ratio of cortical volume to recipient weight has been associated with diminished graft function at 36 months (45)(46)(47). Hence, volumetric measurements are now becoming an important tool in selecting laterality, along with nephron dose matching with the recipient (Figure 7).…”
Section: Computed Tomographymentioning
confidence: 99%
“…17,18 Renal parenchymal volume measurements have also been shown to be accurate in estimating differential renal function in normal and urinary obstructed patients. 19 For kidney cancer patients, Jeon et al have similarly demonstrated that preoperative total kidney volume showed significant correlation with the Cockcroft-Gault formula for baseline GFR (CG-GFR) and that postoperative CG-GFR at 1 year was positively associated with preoperative volume of the normal side.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported an association between transplant kidney volume estimated using CT and long-term recipient renal function. 6,30,31 Further studies in this field might be facilitated by the routine implementation of the ellipsoid technique for renal volume estimation, one that is relatively easily added to the routine clinical workflow of radiologists or urologists. 18 Lastly, having used a convenience sample of relatively few patients, only 2 reviewers, and 1 type of specialized 3D volumetric software, future studies involving more patients and reviewers are required to validate our findings.…”
Section: Discussionmentioning
confidence: 99%